The Effect of Self-Efficacy in Career Decision Making in Students of the Faculty of Education and Psychology, Semarang State University - Najwa Husniyatin Nadhiroh; Kusnarto Kurniawan (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of self-efficacy on career decision making in students of the Faculty of Education and Psychology, State University of Semarang. The study used a quantitative approach with an explanatory design involving 115 students from the class of 2022 as a sample selected using the proportionate stratified random sampling technique. Data were collected through questionnaires measuring self-efficacy and career decision-making based on Bandura's theory of self-efficacy and David V. Tiedeman's theory of career decision-making. The results showed a positive and significant relationship between self-efficacy and career decision-making (r = 0.712; p < 0.01). Simple linear regression analysis yielded the equation Y = 57.305 + 0.379X with a t-value of 10.781 and a significance of 0.000 < 0.05, indicating a significant influence. The determination coefficient (R²) of 0.507 showed that self-efficacy contributed 50.7% to the variation in student career decision-making. These findings confirm that students with high levels of self-efficacy tend to be more confident and better able to make career decisions compared to students with low self-efficacy.